Urban Area Entities in Affecting Regional Development: A Case Study for Mebidangro - Muhammad Taufiq; Benedictus Kombaitan (Department of Urban and Regional Planning, Diponegoro University, 2019)
How is an urban area influencing regional development? Urban area development policy with the primary purpose of driving its surrounding area development found a shift in meaning under the latest development. It initiates a complex relation between cities as network dots, which is not globally separable. This study aims to provide a theoretical analysis regarding its considerations and implications in practice through a study case of the Mebidangro urban area (Medan City-Binjai City-Deli Serdang District-Karo District) in North Sumatra Province, Indonesia. By using a content analysis method, the study evaluates the regional development policy. The result shows that Mebidangro urban area plays a role in influencing regional development through four entities: i.e., reducing income disparity, the centrality of productions and services, urbanization under the mobility context of labor and knowledge, and regional and international cooperation. The study also found that there is a tendency in which nowadays cities are not seen as a hierarchy. However, cooperation functions and its limits are global (world cities networks), not administrative or region. The fact supports an argument that the current area planning context is not only creating its surrounding area development but also as a part of the global city network. Mebidangro is one of the cases that illustrated this concept of operationalization practice. Through existing policy, this urban area was in such a way created to be able to become global city networks as a shifting of regional development planning paradigm from increasing surrounding area development to a region globally compete.